Pore size dynamics control complex volume swelling in pyroptosis - Estelle Bastien; Guillaume Duprez; Hélène Delanoë-Ayari; Hubert Leloup; Charlotte Rivière; Virginie Petrilli; Pierre Recho; Sylvain Monnier (Proceedings of the National Academy of Sciences, 2026)
Pyroptosis, an inflammatory form of cell death, is characterized by massive cell swelling and plasma membrane rupture. Although swelling was recently shown to occur in two steps, the molecular and biophysical mechanisms driving this process remained unclear. Using fast quantitative microscopy, we reveal that between the two swelling phases, cell volume transiently stabilizes despite sustained plasma membrane permeability to ions and small molecules. From a biophysical perspective, the existence of such a plateau is puzzling, as ion pumps should not be able to regulate cell volume under these conditions. To address this, we developed a physical model based on an ion pump and leak framework that incorporates the dynamics of nonselective pore formation. Experimentally, we demonstrate that the plateau phase is controlled by the dynamics of the gasdermin D (GSDMD) pore enlargement, which is modulated by ninjurin-1 (Ninj1) activation, possibly through intracellular calcium. Ninj1-mediated lesions are also required for the second swelling phase. We further show that fully opened GSDMD pores display an effective hydrodynamic radius slightly above 1.9 nm, providing an in situ upper bound for pore size. Together, our findings demonstrate that pyroptotic volume dysregulation emerges from the successive and interdependent actions of GSDMD and Ninj1, each imparting distinct permeability regimes associated with increased water filtration and decreased ion selectivity due to pore opening. These insights bridge molecular and biophysical perspectives on lytic cell death and may inform the broader understanding of membrane rupture in inflammatory and pathological contexts.